MODL-02. GLIOMA ORGANOID MODEL PHENOTYPICALLY RECAPITULATES KEY ASPECTS OF MALIGNANT TRANSFORMATION IN GLIOBLASTOMA. (14th November 2022) - Zhao, Yi; Kant, Shiva; Kesarwani, Pravin; Hubert, Christopher; Nakano, Ichiro; Fullmer, Joseph; Chinnaiyan, Prakash
Abstract: Glioblastoma (GBM) displays extensive intra -tumoral heterogeneity, serving as a major obstacle for effective treatment. The identification of molecular subtypes offered promise for personalized treatment regimens in GBM, however, it has seen been determined these subtypes are reflective of intra - rather than inter -tumoral heterogeneity, with proneural (PN) and mesenchymal (MES) subtypes corresponding to the infiltrative edge and peri-necrotic core of a tumor, respectively. Further, plasticity between subtypes has been identified, with PN-to-MES transition being described as a mode of resistance. Our laboratory utilizes patient-derived, subtype-specific GBM neurospheres as a model to understand GBM heterogeneity and have previously demonstrated that these models faithfully recapitulate human disease, with PN-neurospheres expressing Olig2, having a metabolic phenotype consistent with low-grade glioma, and an indolent growth pattern in vivo when compared to aggressive, CD44 expressing MES-neurospheres. In parallel, our group demonstrated 3D-organoid models of GBM recapitulate the tumor ecology of this malignancy ex vivo . Therefore, we sought to determine if this model could be utilized to provide a window into the plasticity of GBM molecular subtypes. Consistent with their phenotype when grown as neurospheres, MES-organoids had a homogeneous distribution of proliferating cells and retained CD44 expression. In contrast, cellular heterogeneity emerged in PN organoids that could be morphologically divided into an outer, cell-dense rim and an inner core with a lower cell density. The outer rim, recapitulating a perivascular niche, contained proliferating cells, and the inner core contained necrotic cells, mimicking the hypoxic microenvironment of GBM. Intriguingly, PN organoids retained Olig2 expression in the edge, however, actively transitioned into a MES-like state in the core, expressing CD44 and metabolic reprogramming consistent with malignant transformation. Collectively, these finding support that microenvironment contributes towards PN-MES transition and PN organoid models may serve as a tool to provide a window into specific molecular and metabolic factors contributing towards transformation.